Prostate cancer as a first and second cancer: effect of family history - Zhang, H (Nature Publishing Group, 2009)
BACKGROUND: Diagnosis with prostate cancer has been reported to increase the risk of subsequent tumours. However, specific data on individuals with a parental history are not available so far. METHODS: On the basis of the nationwide Swedish Family-Cancer Database including 18,207 primary invasive prostate cancers, standardised incidence ratios (SIRs) were used to estimate the relative risks of subsequent tumours after prostate cancer in the general population and among individuals with a parental history of cancer. RESULTS: A significantly increased SIR of colorectal cancer was found among prostate cancer patients with a parental history of colorectal cancer (2.26, 11 cases). The SIRs of parental concordant (same site) tumours after prostate cancer were also increased for urinary bladder cancer (4.42, 4 cases) and chronic lymphoid leukaemia (38.0, 2 cases). CONCLUSION: A higher than additive and multiplicative interaction was observed between the individual history of prostate cancer and parental history of colorectal and urinary bladder cancers, although the number of cases did not permit the rejection of any interaction model. The results suggest that the occurrence of second tumours, for example bladder after prostate or prostate after bladder tumours, is mostly related to shared genetic and non-genetic risk factors rather than treatment of first cancer.